Ekspresi Programmed Death Ligand-1 (PD-L1) pada Seminoma Testis sebagai Potensi Faktor Prognostik - Boedijono, Freciyana; Tanurahardja, Budiana; Kodariah, Ria (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2020)
BackgroundThe prognosis of testicular seminoma cases which failed to be cured with conventional therapy is poor. Several recurrent eventsafter chemotherapy were also found. PD-L1 is expressed in various types of malignancy and tumor infiltrating lymphocytes (TILs)and its role is known as a prognostic factor. This study was conducted to determine the role of PD-L1 expression seminoma indetermining overall survival (OS) and progression free survival (PFS).MethodsThis is a retrospective cohort study with survival analysis. Clinical data were obtained from medical record in RSUPN CiptoMangunkusumo since January 2011-December 2016 and observed for 2 years. Histopathological data were obtained fromAnatomical Pathology Department and PD-L1 immunohistochemical staining were performed.ResultsA significant correlation between PD-L1 expression in tumor cells with 2-year OS (p=0.023) and PFS (p=0.002) in testicularseminoma was found. No significant correlation between PD-L1 expression in TILs with 2-year OS (p=0.235) and PFS (p=0.111).We also found significant correlations between PD-L1 expression of tumor cells and TILs with PFS (p=0.019). A significantcorrelation between stage with 2-year OS (p=0.010) and PFS (p=0.000) and lymph node metastases with 2-year OS (p=0.010) andPFS (p=0.000).ConclusionPD-L1 expression of testicular seminoma cells were significantly correlated with OS and PFS. There were no statistically significantassociations between PD-L1 expression in TILs with OS and PFS.